Transformation of dental health behavior in elementary school students at a Puskesmas work area: Perubahan perilaku kesehatan gigi pada murid sekolah dasar di suatu wilayah kerja Puskesmas - Grace Monica; Anie Apriani; Monica Ester Teresya (Makassar Dental Journal PDGI Makassar, 2021)
Dental health education was given to all grade I public elementary school students in 2017 using audiovisual media. In 2018, dental health education was carried out with the same theme but with puppet stage extension media. The purpose of this study was to determine changes in dental health behavior in these students. This cross-sectional study involved 96 elementary school students in the working area of ​​Puskesmas Sukawarna, Bandung who were randomly selected with the inclusion criteria having attended dental health education twice in the last two years. Primary data was taken through guided interviews using a questionnaire adapted from the 2013 WHO questionnaire, conducted in 2017 and 2019. In 2017 it was found that 43.8% of students had never received dental care from a dentist, in 2019 only 4.2% of students who never received dental care. In 2017, 8.3% of students did not visit a dentist in the last 12 months, but in 2019 only 3.1%. It was concluded that there was a change in dental health behavior for the better for students who had received dental health education twice in two consecutive years.